Project Management and Engineering Research AEIPRO 2016 - Ayuso Muñoz, José Luis; Yagüe Blanco, José Luis; Capuz-Rizo, Salvador F. (Lecture Notes in Management and Industrial Engineering,, 2017)
This book gathers the best papers presented at the 19th International Congress on Project Management and Engineering, which was held in Granada, Spain in July 2015. It covers a range of project management and engineering contexts, including: civil engineering and urban planning, product and process engineering, environmental engineering, energy efficiency and renewable energies, rural development, information and communication technologies, safety, labour risks and ergonomics, and training in project engineering. Project management and engineering is taking on increasing importance as projects continue to grow in size, more stakeholders become involved, and environmental, organisational and technological issues become more complex. As such, this book offers a valuable resource for all professionals seeking the latest material on the changing face of project management.